Development of integrated chemical kinetic mechanism reduction scheme for diesel and biodiesel fuel surrogates for multi-dimensional CFD applications - Poon, Hiew Mun (2016)
This thesis describes the research undertaken to formulate a systematic chemical kinetic mechanism reduction scheme to generate compact yet comprehensive chemical kinetic models for diesel and biodiesel fuels, for multi-dimensional Computational Fluid Dynamics (CFD) applications. The integrated mechanism reduction scheme was formulated based on the appraisal of various existing mechanism reduction techniques. It consists of five stages including Directed Relation Graph (DRG) with Error Propagation method using Dijkstra’s algorithm, isomer lumping, reaction path analysis, DRG method and adjustment of reaction rate constants. Consequently, a single-component diesel surrogate fuel model with only 79 species (i.e. n-hexadecane (HXNv2)) and a multi-component biodiesel surrogate fuel model (i.e. methyl decanoate/methyl-9-decenoate/n-heptane (MCBSv2)) with only 80 species were successfully derived from their respective detailed mechanisms, which contain thousands of species and elementary reactions. Here, both auto-ignition and jet-stirred reactor (JSR) conditions were applied as the data source for mechanism reduction. An overall 97 % reduction in mechanism size in terms of total number of species as well as an average 97 % reduction in computational runtime in zero-dimensional (0-D) chemical kinetic simulations was achieved. Both HXNv2 and MCBSv2 were also comprehensively validated in 0-D simulations in terms of ignition delay (ID) timings and species concentration profiles. Good agreement between the predictions and measurements was obtained throughout the test conditions.